Wackenroder e Reichardt Musica e letteratura nel primo Romanticismo tedesco - Alcione, Serena (Biblioteca di Studi di Filologia Moderna, 2014)
Wackenroder's conception of music is strongly influenced by the musical thought of the composer Johann Friedrich Reichardt, who was a romantic music teacher, friend and mentor of Wackenroder, whom he introduced to the 'realm of sounds'. Reichardt was the author of numerous essays on music and of the unique Musikerroman from the Enlightenment period (Leben des berühmten Tonkünstlers Heinrich Wilhelm Gulden nachher genannt Guglielmo Enrico Fiorino, 1779). Wackenroder e Reichardt: musica e letteratura nel primo Romanticismo tedesco ("Wackenroder and Reichardt: music and literature in the first German Romanticism") compares the literary works of the two authors and investigates the results of their influence. The work retraces the transition from the conception of music during the Enlightenment, linked to the social function of art, to the idea of an 'absolute' music of the Romantic era, determining the artist's problematic existence.